Purification of the full-length, membrane-associated form of the antiviral enzyme viperin utilizing nanodiscs - Ayesha M. Patel; Karl J. Koebke; Timothy J. Grunkemeyer; Colleen M. Riordan; Youngsoo Kim; Ryan C. Bailey; E. Neil G. Marsh (Scientific Reports, 2022)
Abstract Viperin is a radical S-adenosylmethionine enzyme that catalyzes the formation of the antiviral ribonucleotide, 3’-deoxy-3’,4’-didehydroCTP. The enzyme is conserved across all kingdoms of life, and in higher animals viperin is localized to the ER-membrane and lipid droplets through an N-terminal extension that forms an amphipathic helix. Evidence suggests that the N-terminal extension plays an important role in viperin’s interactions with other membrane proteins. These interactions serve to modulate the activity of various other enzymes that are important for viral replication and constitute another facet of viperin’s antiviral properties, distinct from its catalytic activity. However, the full-length form of the enzyme, which has proved refractory to expression in E. coli, has not been previously purified. Here we report the purification of the full-length form of viperin from HEK293T cells transfected with viperin. The purification method utilizes nanodiscs to maintain the protein in its membrane-bound state. Unexpectedly, the enzyme exhibits significantly lower catalytic activity once purified, suggesting that interactions with other ER-membrane components may be important to maintain viperin’s activity.